Rapidly Signal‐enhanced Metabolites for Atomic Scale Monitoring of Living Cells with Magnetic Resonance. Issue 7 (7th April 2022) - Ding, Yonghong; Korchak, Sergey; Mamone, Salvatore; Jagtap, Anil P.; Stevanato, Gabriele; Sternkopf, Sonja; Moll, Denis; Schroeder, Henning; Becker, Stefan; Fischer, André; Gerhardt, Ellen; Outeiro, Tiago F.; et al.
Abstract: Nuclear magnetic resonance (NMR) is widely applied from analytics to biomedicine although it is an inherently insensitive phenomenon. Overcoming sensitivity challenges is key to further broaden the applicability of NMR and, for example, improve medical diagnostics. Here, we present a rapid strategy to enhance the signals of 13 C‐labelled metabolites with para ‐hydrogen and, in particular, 13 C‐pyruvate, an important molecule for the energy metabolism. We succeeded to obtain an average of 27 % 13 C polarization of 1‐ 13 C‐pyruvate in water which allowed us to introduce two applications for studying cellular metabolism. Firstly, we demonstrate that the metabolism of 1‐ 13 C‐pyruvate can serve as a biomarker in cellular models of Parkinson's disease and, secondly, we introduce the opportunity to combine real‐time metabolic analysis with protein structure determination in the same cells. Based on the here presented results, we envision the use of our approach for future biomedical studies to detect diseases. Abstract : A rapid magnetic resonance signal enhancements approach to amplify metabolic signals is introduced, used for cellular investigations and shows first evidence to work as a biomarker for Parkinson's disease.